A perspective on supplier selection and order allocation: Literature review - Trish Nguyen; Saman Hassanzadeh Amin; Bharat Shah (Administrative Sciences, 2024)
Purchasing and procurement managers should make informed decisions in selecting materials at the right time, in sufficient quantities, and at affordable prices. Supplier selection and order allocation (SSOA) is a vital aspect of purchasing and procurement processes. In this research, the techniques and decision-making methods used in SSOA from peer-reviewed journals published from 2021 to 2023 are examined. This research explores the publications through three major categories, including literature reviews (LR), deterministic optimization (DO) models, and uncertain optimization (UO) models. The related operations research techniques are also discussed. Furthermore, observations, conclusions, and suggestions for future studies are provided with details.
Keywords: 350; multi-objective programming; operations research; supplier selection and order allocation; supply chain management